Acts of violence in contemporary Russian drama - Szymańska, Aleksandra (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The starting point for the analyses has been Mark Lipovetsky and Birgit Beumers’ study „Performing Violence”, which investigates the violent portrayal of the identity crisis of a generation in 21st-century Russian theatrical works. In the present paper, three dramas by contemporary Russian playwrights – Ksenia Dragunskaya, the Presnyakov brothers and Farid Nagim – are analyzed. In their plays they concentrate on the dynamic changes taking place in the sphere of public life in the post-Soviet country. A dominant feature of their plays is the deep crisis of identity of the post-Soviet society which manifests itself in acts of communicative violence.